2003
DOI: 10.1111/j.1151-2916.2003.tb03557.x
|View full text |Cite
|
Sign up to set email alerts
|

A New Glycothermal Process for Barium Titanate Nanoparticle Synthesis

Abstract: Barium titanate (BaTiO3) nanoparticles were synthesized at the low temperature of 80°C through a glycothermal reaction using Ba(OH)2·8H2O and amorphous titanium hydrous gel as precursors and a solution of 1,4‐butanediol and water as solvent. This processing method provides a simple low‐temperature route for producing BaTiO3 nanoparticles, which could also be extended to other systems. It is demonstrated that the size of BaTiO3 particles can be controlled by reaction conditions, such as reaction temperature and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 11 publications
0
18
0
Order By: Relevance
“…Most literatures about solvothermal BaTiO 3 did not investigate the dissolvability of Ba(OH) 2 · 8H 2 O in nonaqueous solvent. In addition, among these, although newly-prepared amorphous TiO 2 or Ti(OH) 4 gel having the best active reactivity of all Ti-precursors for the production of BaTiO 3 nanopowder via solvothermal (hydrothermal) method had already been testified by many researchers [9,16,17], it brought about more experimental steps to result in high industry cost.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Most literatures about solvothermal BaTiO 3 did not investigate the dissolvability of Ba(OH) 2 · 8H 2 O in nonaqueous solvent. In addition, among these, although newly-prepared amorphous TiO 2 or Ti(OH) 4 gel having the best active reactivity of all Ti-precursors for the production of BaTiO 3 nanopowder via solvothermal (hydrothermal) method had already been testified by many researchers [9,16,17], it brought about more experimental steps to result in high industry cost.…”
Section: Introductionmentioning
confidence: 98%
“…B.K. Kim et al [17] glycothermally synthesized BaTiO 3 using Ba(OH) 2 · 8H 2 O and titanium isopropoxide as precursors and 1,4-butanediol as solvent under autogeneous vapor pressures. They found that glycolic solution acted as a strong oxidizer instead of the highly alkaline conditions in the hydrothermal reaction.…”
Section: Introductionmentioning
confidence: 99%
“…However, there have been few studies on glycothermal synthesis of ferroelectric materials. In a previous study, we have shown that glycothermal processing method provides a simple low temperature route for producing cubic BaTiO 3 nanoparticles, which could also be extended to other systems [28].…”
Section: Introductionmentioning
confidence: 99%
“…However, in the ethanolthermal condition, the cubic and tetragonal forms will coexist in the bartium titanate particles [12]. Many researchers believed that the strains that develop in the particles prevent it from assuming the tetragonal form and that the presence of hydroxyl impurities in the lattice lead to defects and result in microstrains that keep the particles cubic, which is also responsible for the lower dielectric constant.…”
Section: Resultsmentioning
confidence: 99%